Gain and noise figure improvements in double-pass S-band EDFA - HARUN, S; AHMAD, H (ELSEVIER SCI LTD, 2007)
Double-pass short-wavelength band erbium-doped fiber amplifier (S-band EDFA) with enhanced gain and noise figure characteristics is demonstrated. It uses a broadband fiber Bragg grating (FBG) operating in conventional-band (C-band) region to reduce the C-band amplified spontaneous emission (ASE) in the amplifier system and thus increases the population inversion in the S-band region. The small signal gain is increased by about 2.7 dB for 1500 nm signal at pump power of 103 mW, compared with that of the conventional double-pass amplifier without the FBG. The corresponding noise figure is also improved by 0.5 dB. (c) 2006 Elsevier Ltd. All rights reserved.